1984
DOI: 10.1210/jcem-58-3-430
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin and Prolactin Levels in Follicular Fluid of Human Ova Successfully Fertilized in Vitro

Abstract: Follicular fluid (FF) and oocytes were obtained from 94 follicles of 36 women for fertilization in vitro. Ovulation was induced with human menopausal gonadotropin, and follicular aspiration was performed 36 h after an ovulatory injection of hCG. The concentrations of immunoreactive hCG, FSH, and PRL were correlated with the degree of maturation of the oocyte-corona-cumulus complex mass (OCCC), fertilization, rate of cleavage, and the incidence of pregnancy after embryo transfer. Immature OCCC were derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…However, in studies evaluating follicular fluid FSH levels in fertilized and unfertilized oocytes, the results have varied. While Laufer et al (5) found higher levels of follicular fluid FSH in oocytes that were successfully fertilized compared to those that did not fertilize, others (4,18) found no significant difference between the two groups. Salustfi et al proposed that FSH induced an increase in cAMP in the cumulus-enclosed mouse oocyte, and that may also promote an increase in cAMP turnover in the cumulus complex, leading to an increase in germinal vesicle breakdown (19).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, in studies evaluating follicular fluid FSH levels in fertilized and unfertilized oocytes, the results have varied. While Laufer et al (5) found higher levels of follicular fluid FSH in oocytes that were successfully fertilized compared to those that did not fertilize, others (4,18) found no significant difference between the two groups. Salustfi et al proposed that FSH induced an increase in cAMP in the cumulus-enclosed mouse oocyte, and that may also promote an increase in cAMP turnover in the cumulus complex, leading to an increase in germinal vesicle breakdown (19).…”
Section: Discussionmentioning
confidence: 94%
“…Investigators have studied the hormone levels of the follicular fluid of developing oocytes in both natural and stimulated cycles (1)(2)(3)(4)(5). In the natural cycle, Seibel et al (27) measured the follicular fluid levels in healthy oocytes and found no difference in Ez and androstenedione levels at any stage of oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a controversy about the value of FF prolactin levels in predicting pregnancy. Some researchers suggested that PRL concentration of FF might be an additional parameter of oocyte maturation and fertilizability (35,36). However, others suggested that higher levels of prolactin has adverse effects or no impact on pregnancy outcome (37,38).…”
Section: Discussionmentioning
confidence: 99%